'Birth work' accompaniment and PhD supervision: an alternative feminist pedagogy for the neoliberal university. Issue 1 (2nd January 2019) - Fannin, Maria; Perrier, Maud
ABSTRACT: In this paper, we discuss how 'with-woman' midwifery and doula care provide resources for rethinking the theory and practice of academic supervision from a feminist perspective. We identify how the tradition of accompaniment in both birth work and academia is under threat given the economic reforms facing public sector education and health care. Despite these pressures, we suggest that the practice of focusing on the pregnant woman as an 'expert' on her pregnancy rather than on the foetus or the delivery – that is, the 'product' of her pregnancy – would help transform how we theorise and practise academic supervision. The aim of the supervisory relation would mean supporting the student's direct relation to the intellectual, embodied and emotional process of completing the PhD. Such an approach suggests ways in which the pedagogical practices of contemporary midwifery and doula care can inform academic supervision in the neoliberal university.